Constitutional faith - Levinson, Sanford, 1941- (Princeton University Press, 2011)
This book examines the "constitutional faith" that has, since 1788, been a central component of American "civil religion." By taking seriously the parallel between wholehearted acceptance of the Constitution and religious faith, Sanford Levinson opens up a host of intriguing questions about what it means to be American. While some view the Constitution as the central component of an American religion that serves to unite the social order, Levinson maintains that its sacred role can result in conflict, fragmentation, and even war.